THE CONCEPT OF SYNTACTIC VARIABILITY IN THE CONTEXT OF LEARNING A FOREIGN LANGUAGE - Aymanova, Sh. (SCIENCE and SOCIETY, 2025)
This article deals with the syntactic variability, the capacity to produce and comprehend diverse sentence structures, plays a crucial role in mastering a foreign language. This concept encompasses the flexibility to use various syntactic forms and adapt sentence constructions depending on the communicative situation, purpose, and cultural context. The author states that in the classroom, focusing on syntactic variability can foster a dynamic learning environment where students experiment with different sentence structures and observe how subtle changes impact meaning.